2004
DOI: 10.1021/ja049474e
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Electrophilic Amination of Diorganozinc Reagents

Abstract: The copper-catalyzed electrophilic amination of diorganozinc reagents employing O-acyl N,N-dialkyl hydroxylamine derivatives as aminating agents is described. This reaction offers a general method for the preparation of tertiary amines in high yields and is noteworthy for its convenience both in terms of reaction conditions employed (room temperature,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
99
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(102 citation statements)
references
References 18 publications
0
99
0
3
Order By: Relevance
“…Primary O ‐benzoyl hydroxylamines, however, worked poorly in the reaction. To address this shortcoming, we experimented with the transmetalation of intermediate 6 with zinc; pioneering work from Johnson has shown that arylzinc compounds can react with primary O ‐benzoyl hydroxylamines under copper catalysis to give secondary anilines 13. We were pleased to find that the addition of ZnCl 2 (0.5 equiv) to the reaction mixture was successful, enabling i PrNHOBz and CyNHOBz to be used as electrophiles in the reaction ( 7 k , 7 l ) in 44 and 46 % yield, respectively.…”
mentioning
confidence: 99%
“…Primary O ‐benzoyl hydroxylamines, however, worked poorly in the reaction. To address this shortcoming, we experimented with the transmetalation of intermediate 6 with zinc; pioneering work from Johnson has shown that arylzinc compounds can react with primary O ‐benzoyl hydroxylamines under copper catalysis to give secondary anilines 13. We were pleased to find that the addition of ZnCl 2 (0.5 equiv) to the reaction mixture was successful, enabling i PrNHOBz and CyNHOBz to be used as electrophiles in the reaction ( 7 k , 7 l ) in 44 and 46 % yield, respectively.…”
mentioning
confidence: 99%
“…[15,17,21,22] However, electrophilic amination of organometallic reagents by R 1 R 2 N + synthons, [23][24][25][26][27][28][29][30][31] though conceptually feasible, has received much less attention. [32][33][34][35][36][37] The putative catalytic cycle of this transformation is illustrated in Scheme 1: (1) reaction of R 1 R 2 N À X (as an electrophile) with the metal catalyst (M 1 ) would introduce the amine group to the metal center to form R 1 R 2 N-M 1 -X; [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] (2) transmetalation of RM 2 (M 2 = B(OH) 2 ) with R 1 R 2 N-M 1 -X to furnish R 1 R 2 N-M 1 R; and (3) final reductive elimination to form the CÀN bond.The groups of Liebeskind and Johnson have studied this type of CÀN bond formation employing NÀO derivatives. [32][33][34][35][36][37] N-Chloroamides, though attractive because of the ease of preparation [49][50][51] and the high activities of the N À Cl bond, …”
mentioning
confidence: 99%
“…[32][33][34][35][36][37] The putative catalytic cycle of this transformation is illustrated in Scheme 1: (1) reaction of R 1 R 2 N À X (as an electrophile) with the metal catalyst (M 1 ) would introduce the amine group to the metal center to form R 1 R 2 N-M 1 -X; [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] (2) transmetalation of RM 2 (M 2 = B(OH) 2 ) with R 1 R 2 N-M 1 -X to furnish R 1 R 2 N-M 1 R; and (3) final reductive elimination to form the CÀN bond.…”
mentioning
confidence: 99%
“…Reported bases for this transformation include sodium carbonate, 22 sodium hydroxide, 24 tertbutylamine 25 and disodium hydrogen phosphate. 26 Pleasingly, caesium carbonate was found to be effective in the reaction of primary amines with benzoyl peroxide allowing for the direct conversion of primary amines to ketones. Treatment of a cooled DMF solution of caesium carbonate (1.5 equivalents) and benzoyl peroxide (1 equivalent) with the primary amine (1.2 equivalents) followed by warming of the reaction mixture led directly to the corresponding ketone ( Table 3).…”
Section: Methodsmentioning
confidence: 99%